2008
DOI: 10.5194/acp-8-3337-2008
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on air pollution levels in the Northern Hemisphere with special focus on Europe and the Arctic

Abstract: Abstract. The response of a selected number of chemical species is inspected with respect to climate change. The coupled Atmosphere-Ocean General Circulation Model ECHAM4-OPYC3 is providing meteorological fields for the Chemical long-range Transport Model DEHM. Three selected decades (1990s, 2040s and 2090s) are inspected. The 1990s are used as a reference and validation period. In this decade an evaluation of the output from the DEHM model with ECHAM4-OPYC3 meteorology input data is carried out. The model res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 24 publications
5
59
0
Order By: Relevance
“…Meleux et al, 2007 in their study of summer European ozone reported that temperature driven increase in biogenic emissions appeared to enhance ozone production and isoprene was identified to be the most important chemical factor in the ozone sensitivity. The same conclusion was reached by Hedegaard et al (2008) with their modeling study of climate change on air pollution, suggesting that dominating impacts on a large number of species including ozone are related to temperature increase. Figure 4 (left panel) shows differences in near surface air temperature between the ECHAM and ERA run during winter.…”
Section: Temperature and Pbl Heightsupporting
confidence: 59%
See 1 more Smart Citation
“…Meleux et al, 2007 in their study of summer European ozone reported that temperature driven increase in biogenic emissions appeared to enhance ozone production and isoprene was identified to be the most important chemical factor in the ozone sensitivity. The same conclusion was reached by Hedegaard et al (2008) with their modeling study of climate change on air pollution, suggesting that dominating impacts on a large number of species including ozone are related to temperature increase. Figure 4 (left panel) shows differences in near surface air temperature between the ECHAM and ERA run during winter.…”
Section: Temperature and Pbl Heightsupporting
confidence: 59%
“…Most of the studies investigating the future air quality projections were based on global Climate-Chemistry models or global climate models coupled to chemistry-transport models (Hauglustaine et al, 2005;Stevenson et al, 2006;Racherla and Adams, 2006;Hedegaard et al, 2008;Racherla and Adams, 2008 and references therein) and only few studies give emphasis on the regional scale future air-quality (Szopa et al, 2006;Meleux et al, 2007;Nolte et al, 2008;Kruger et al, 2008). This paper presents climate-air quality simulations over Europe on a decadal timescale with focus on the sensitivity of near surface ozone on the lateral meteorological boundary conditions constraining the climate model.…”
Section: Introductionmentioning
confidence: 99%
“…For Europe, the measurements used for this evaluation originates from the EMEP measuring network, which includes a large number of chemical components. Details about the measurement period and the location of the measuring sites are presented in Hedegaard et al (2008). For the North American domain, the monitoring data of the hourly ozone concentrations are provided by the US Environmental Protection Agency (EPA).…”
Section: Measuring Networkmentioning
confidence: 99%
“…Climate-chemistry interactions and the evolution of air quality over the coming decades depend on many factors, such as the growth of pollutant emissions due to worldwide economic development, localized emissions in high activity areas such as megacities, and changes in climatic factors such as temperature and precipitation. Many recent studies focusing on the impact of increased greenhouse gas concentrations on air quality have found an increase in tropospheric ozone as temperatures and greenhouse gas concentrations increase (e.g., Hogrefe et al, 2011;Andersson and Engard, 2010;Weaver et al, 2009;Zhang et al, 2008;Leibenspeger et al, 2008;Hedegaard et al, 2008;Meleux et al, 2007;Giorgi and Meleux, 2007;Forkel and Knoche, 2006;Stevenson et al, 2005;Langner et al, 2005). Specifically, ozone is an important component in the troposphere because (1) it is a leading indicator of poor air quality that adversely affects human health and natural ecosystems (e.g., WHO, 2003) and (2) has the ability to act as a greenhouse gas.…”
Section: Introductionmentioning
confidence: 99%